Religion in the modern Belarus: the problem of the change of the picture of the world - Adzinochanka, Viktar A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The problem of changing the picture of the world in modern Belarusian religious studies is considered. Changes in approaches to the study of religion are analyzed in the context of the overall situation of the transformation of Belarusian society. The author proceeds from the fact that the very social reality has changed, which was the main reason for the changes in the treatment of religion. A comparative analysis of the world’s pictures in scientific atheism and religious studies is given. The interpretation of the scientific picture of the world, developed within the framework of the Minsk Methodological School, is used. The problem of correlation between the scientific and religious picture of the world is analyzed. The possibility of solving this problem on the basis of the principle of methodological agnosticism is considered. The following processes that influence the change of the world picture in modern Belarusian religious studies are highlighted in the article: the change of attitudes towards religion on the part of the state and society, increased attention to the spatial and temporal localization of Belarus in connection with the formation of an independent Belarusian state, the complexity of the world picture in modern natural science And social sciences. It is alleged that in the situation of transformation of modern Belarusian society, the picture of the world in religious studies will also change.